Breaking dawn - Meyer, Stephanie (Hachette india London, 2014)
To be irrevocably in love with a vampire is both fantasy and nightmare woven into a dangerously heightened reality for Bella Swan. Pulled in one direction by her intense passion for Edward Cullen, and in another by her profound connection to werewolf Jacob Black, she has endured a tumultuous year of temptation, loss and strife to reach the ultimate turning point. Her imminent choice to either join the dark but seductive world of immortals or pursue a fully human life has become the thread from which the fate of two tribes hangs. Now that Bella has made her decision, a startling chain of unprecedented events is about to unfold with potentially devastating and unfathomable consequences. Just when the frayed strands of Bella's life - first discovered in "Twilight", then scattered and torn in "New Moon" and "Eclipse" - seem to heal and knit together, could they be destroyed... forever?Please ask if you need a specific version. The data provided here may not be correct. With buying and not asking you are accepting the book as is.